The Strengthening Emotional Regulation of Children with Intellectual Disabilities through Social-Emotional Group Guidance in Inclusive Primary Schools - Maulina, Arum; Rudi Masrukhin, Akhmad; Faisol Hakim (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Emotional regulation is a critical developmental competence for children with intellectual disabilities, particularly in inclusive primary school settings. This study examined the strengthening of emotional regulation through social-emotional group guidance. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. Participants consisted of six children with intellectual disabilities enrolled in an inclusive primary school. Emotional regulation was assessed using a structured observational scale administered before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a statistically significant difference between pretest and posttest scores (Z = −2.201; p = 0.031), indicating a gradual improvement in emotional regulation following the group guidance program. These findings suggest that social-emotional group guidance is a relevant and developmentally appropriate approach to supporting emotional regulation within school-based counseling services in inclusive education.